Coats Syndrome in Facioscapulohumeral Dystrophy Type 1 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at University of Rochester Medical Center, NY; Hopital Archet-CHU de Nice, France; and Albert Einstein College of Medicine, NY, studied the frequency of Coats syndrome and its association with D4Z4 contraction size in 408 patients identified with facioscapulohumeral dystrophy type 1 (FSHD1).